Understanding Mental Health App Use Among Attendees of Primary Health Care in Taif, Saudi Arabia - Sawsan Alkhammash; Mugtaba Osman (BJPsych Open, 2025)
Aims: Mental health apps are increasingly available and accessible to the public. Global research indicated variable rates of use among people with main barriers identified are cost, privacy concerns, and difficulty of use. Little is known about prevalence and barriers of use of mental health apps in Saudi Arabia.